c1 A= 7.(-10)+(-10).2
c2B=8.(-35)+(-35).2
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a, 26 + 35 + 21 + 18 + 35 + 14 + 10 + 10 + 110 + 14 + 120 + 8 + 8 + 7 + 22 + 32.
=490
b, 6 + 10 + 8 + 2 + 2 + 24 + 2 + 3.
=57
a) -( -35 + 7 - 13 ) + ( 2 - 35 ) - ( 13 - 7 )
= 35 - 7 + 13 + 2 - 35 - 13 + 7
= ( 35 - 35 ) + ( -7 + 7 ) + ( 13 - 13 ) + 2
= 0 + 0 + 0 + 2
= 2
b) ( 70 + 8 - 35 ) - ( 8 - 37 - 10 ) - 70
= 70 + 8 - 35 - 8 + 37 + 10 - 70
= ( 70 - 70 ) + ( 8 - 8 ) + ( -35 + 37 ) + 10
= 0 + 0 + 2 + 10
= 12
c) 5 - ( 14 + 4 - 52 ) - ( 52 - 14 ) + 4
= 5 - 14 - 4 + 52 - 52 + 14 + 4
= 5 - ( 14 + 14 ) + ( 52 - 52 ) + ( -14 + 14 )
= 5 - 14 - 14 + 0 + 0
= 5 - ( 14 - 14 )
= 5 - 0
= 5
b: Ta có: \(\left(\sqrt{7-3\sqrt{5}}\right)\cdot\left(7+3\sqrt{5}\right)\cdot\left(3\sqrt{2}+\sqrt{10}\right)\)
\(=\left(3-\sqrt{5}\right)\left(3+\sqrt{5}\right)\left(7+3\sqrt{5}\right)\)
\(=4\left(7+3\sqrt{5}\right)\)
\(=28+12\sqrt{5}\)
Lời giải:
a.
$A=\sqrt{8+\sqrt{55}}-\sqrt{8-\sqrt{55}}-\sqrt{125}$
$\sqrt{2}A=\sqrt{16+2\sqrt{55}}-\sqrt{16-2\sqrt{55}}-\sqrt{250}$
$=\sqrt{(\sqrt{11}+\sqrt{5})^2}-\sqrt{(\sqrt{11}-\sqrt{5})^2}-5\sqrt{10}$
$=|\sqrt{11}+\sqrt{5}|-|\sqrt{11}-\sqrt{5}|-5\sqrt{10}$
$=2\sqrt{5}-5\sqrt{10}$
$\Rightarrow A=\sqrt{10}-5\sqrt{5}$
b.
$B=\sqrt{7-3\sqrt{5}}.(7+3\sqrt{5})(3\sqrt{2}+\sqrt{10})$
$B\sqrt{2}=\sqrt{14-6\sqrt{5}}(7+3\sqrt{5})(3\sqrt{2}+\sqrt{10})$
$=\sqrt{(3-\sqrt{5})^2}(7+3\sqrt{5}).\sqrt{2}(3+\sqrt{5})$
$=(3-\sqrt{5})(7\sqrt{2}+3\sqrt{10})(3+\sqrt{5})$
$=(3^2-5)(7\sqrt{2}+3\sqrt{10})$
$=4(7\sqrt{2}+3\sqrt{10})=28\sqrt{2}+12\sqrt{10}$
$\Rightarrow B=28+12\sqrt{5}$
c.
$C=\sqrt{2}(\sqrt{7}-\sqrt{5})(6-\sqrt{35})\sqrt{6+\sqrt{35}}$
$=(\sqrt{7}-\sqrt{5})(6-\sqrt{35})\sqrt{12+2\sqrt{35}}$
$=(\sqrt{7}-\sqrt{5})(6-\sqrt{35})\sqrt{(\sqrt{7}+\sqrt{5})^2}
$=(\sqrt{7}-\sqrt{5})(6-\sqrt{35})(\sqrt{7}+\sqrt{5})$
$=(7-5)(6-\sqrt{35})$
$=2(6-\sqrt{35})=12-2\sqrt{35}$
d: \(=\dfrac{-7}{9}\left(\dfrac{3}{11}+\dfrac{8}{11}\right)+1+\dfrac{7}{9}=1\)
e: \(=\dfrac{1}{5}\left(\dfrac{10}{19}+\dfrac{9}{19}\right)-\dfrac{2}{35}=\dfrac{1}{5}-\dfrac{2}{35}=\dfrac{5}{35}=\dfrac{1}{7}\)
f: \(=\left(-25\cdot4\right)\cdot\left(-8\cdot125\right)\cdot\left(-17\right)=-1700000\)
14) \(\sqrt{7-4\sqrt{3}}=2-\sqrt{3}\)
15) \(\sqrt{8+2\sqrt{15}}=\sqrt{5}+\sqrt{3}\)
16) \(\sqrt{10-2\sqrt{21}}=\sqrt{7}-\sqrt{3}\)
17) \(\sqrt{11+2\sqrt{18}}=3+\sqrt{2}\)
18) \(\sqrt{7+2\sqrt{10}}=\sqrt{5}+\sqrt{2}\)
19) \(\sqrt{7+4\sqrt{3}}=2+\sqrt{3}\)
20) \(\sqrt{12-2\sqrt{35}}=\sqrt{7}-\sqrt{5}\)
câu 1: A=-10x(2+7)
=-10x9
=-90
câu 2 B=-35x(2+8)
=-35x10
=-350
\(A=7.\left(-10\right)+\left(-10\right).2\)
\(=-10\left(7+2\right)\)
\(=-10.9\)
\(=-90\)